Evaluating the Effectiveness of Spousal Testing Among Syphilis-Infected Pregnant Women in the Context of Mother-to-Child Transmission Elimination: A Multicenter Study in Southeastern China - Xue X; Huang X; Liu G; Jiang X; Lin W; Chen Y; Huang C (Risk Management and Healthcare Policy)
Xiaomeng Xue,1,2,* Xinxin Huang,3,* Guihua Liu,2 Xiumin Jiang,2 Wenzhao Lin,1,2 Yongfan Chen,1,2 Chengyu Huang1,2 1School of Nursing, Fujian Medical University, Fuzhou, Fujian, People’s Republic of China; 2Nursing Department, Fujian Maternity and Child Health Hospital, College of Clinical Medicine for Obstetrics and Gynecology and Pediatrics, Fujian Medical University, Fuzhou, Fujian, People’s Republic of China; 3The Ministry of Health, Fujian Maternity and Child Health Hospital, College of Clinical Medicine for Obstetrics and Gynecology and Pediatrics, Fujian Medical University, Fuzhou, Fujian, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiumin Jiang, Nursing Department, Fujian Maternity and Child Health Hospital, College of Clinical Medicine for Obstetrics and Gynecology and Pediatrics, Fujian Medical University, No. 18. Daoshan Road, Fuzhou, Fujian, People’s Republic of China, Email jiangxiumin@fjsfy.comPurpose: Syphilis during pregnancy poses significant risks to maternal and neonatal health. Spousal testing is crucial for preventing congenital syphilis transmission. This study assessed spousal testing rates among syphilis-positive pregnant women to guide public health interventions.Methods: This multicenter effectiveness study was conducted in Southeast China, utilizing data from the Chinese HIV/AIDS, Syphilis, and Hepatitis B Prevention Information System between 2018 to 2024. Proportions were used to describe the sociodemographic characteristics of pregnant women with syphilis. Univariate and multivariate unconditional logistic regression models were used to analyze the factors associated with the testing status of spouses of pregnant women with syphilis.Results: A total of 4,875 spouses were tested for syphilis. Older gestational age at the first prenatal visit (aOR = 1.014, 95% CI: 1.007– 1.022) and at delivery (aOR = 1.273, 95% CI: 1.011– 1.602) were associated with lower rates of spousal testing. Spouses of women reported in 2022– 2023 (aOR = 1.840, 95% CI: 1.465– 2.311) had a higher likelihood of being untested. Unmarried status (aOR = 1.181, 95% CI: 1.022– 1.364), junior high school education and below (aOR = 1.244, 95% CI: 1.121– 1.381), no history of infection (aOR = 2.281, 95% CI: 2.073– 2.510), and prenatal care in Grade II hospitals (aOR = 0.1.292, 95% CI: 1.140– 1.464) were risk factors for spousal testing.Conclusion: From 2018 to 2024, the spousal testing rate was 60%, with a syphilis positivity rate of 14.7%. Data revealed multiple risk factors, such as a late first pregnancy test, advanced age, unmarried status, lower education level, no history of syphilis infection, and selection of prenatal care in Grade II hospitals as delivery facilities. Recommendations include establishing specialized clinics, post-test spousal counseling, and routine spousal testing.Plain Language Summary: Syphilis is a worldwide epidemic infectious disease that poses a great threat to the health of newborns through sexual transmission and mother-to-child transmission. The incidence of syphilis is still high in China. Prevention of sexually transmitted infections is considered to be a key factor in the prevention of syphilis. The spouses of pregnant women with syphilis may act as vectors of infection, which increases the risk of syphilis infection in newborns. This study provides an in-depth analysis of the factors that affect the testing rate of the spouses of pregnant women with syphilis under the strategy of elimination of mother-to-child transmission (EMTCT) in Southeast China. The results revealed that the spousal testing rate increased from 2018 to 2024, whereas the syphilis positive rate among spouses was relatively high. The data revealed multiple risk factors, such as late first pregnancy test, advanced age, unmarried status, low education level, no previous history of syphilis infection, and selection of prenatal care in Grade II hospitals for delivery. This study validated the effectiveness of the EMTCT framework in reducing mother-to-child transmission of syphilis and highlighted the specific measures of the risk factors mentioned above in the future control of sexual and mother‒to-child transmission of syphilis.Keywords: syphilis, pregnant woman, spousal testing, multicenter, influencing factors